Developing A Sense Of National Pride In Students Through Teaching The History Of Temuria (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
In the article, in the history classes in the general education system, by telling about the bravery of the national heroes for the nation, to develop feelings of national pride in students, to encourage them to search, to find and analyze the data themselves, to teach the students how to work with data, how and where to search for data, how to compare, what to base the comparison on. feedback on the teaching of knowledge and skills such as